FGF21 regulates hepatic metabolic pathways to improve steatosis and inflammation. Issue 8 (August 2020) - Keinicke, Helle; Sun, Gao; Mentzel, Caroline M Junker; Fredholm, Merete; John, Linu Mary; Andersen, Birgitte; Raun, Kirsten; Kjaergaard, Marina
Abstract : The prevalence of non-alcoholic fatty liver disease (NAFLD) has increased dramatically worldwide and, subsequently, also the risk of developing non-alcoholic steatohepatitis (NASH), hepatic fibrosis, cirrhosis and cancer. Today, weight loss is the only available treatment, but administration of fibroblast growth factor 21 (FGF21) analogues have, in addition to weight loss, shown improvements on liver metabolic health but the mechanisms behind are not entirely clear. The aim of this study was to investigate the hepatic metabolic profile in response to FGF21 treatment. Diet-induced obese (DIO) mice were treated with s.c. administration of FGF21 or subjected to caloric restriction by switching from high fat diet (HFD) to chow to induce 20% weight loss and changes were compared to vehicle dosed DIO mice. Cumulative caloric intake was reduced by chow, while no differences were observed between FGF21 and vehicle dosed mice. The body weight loss in both treatment groups was associated with reduced body fat mass and hepatic triglycerides (TG), while hepatic cholesterol was slightly decreased by chow. Liver glycogen was decreased by FGF21 and increased by chow. The hepatic gene expression profiles suggest that FGF21 increased uptake of fatty acids and lipoproteins, channeled TGs toward the production of cholesterol and bile acid, reduced lipogenesis and increased hepatic glucose output. Furthermore, FGF21 appeared to reduce inflammation and regulate hepatic leptin receptor-a expression. In conclusion, FGF21 affected several metabolic pathways to reduce hepatic steatosis and improve hepatic health and markedly more genes than diet restriction (61 vs 16 out of 89 investigated genes).